Evolution of equine influenza virus in vaccinated horses - Murcia, Pablo R.; Baillie, Gregory J.; Stack, J. Conrad; Jervis, Carley; Elton, Debra; Mumford, Jennifer A.; Daly, Janet M.; Kellam, Paul; Grenfell, Bryan T.; Holmes, Edward C.; Wood, James L.N. (American Society for Microbiology, 2013)
Influenza A viruses are characterized by their ability to evade host immunity, even in vaccinated individuals. To determine how prior immunity shapes viral diversity in vivo, we studied the intra- and interhost evolution of equine influenza virus in vaccinated horses. Although the level and structure of genetic diversity were similar to those in naive horses, intrahost bottlenecks may be more stringent in vaccinated animals, and mutations shared among horses often fall close to putative antigenic sites.